IoT Security: Threats and Possible Solutions - Andrei-Robert CAZACU (Informatică economică, 2022)
Despite IoT being in the spotlight for several years now, Gartner still predicts a five time increase in number of devices from 2018 to 2028 [1], up to 1.9 billion units, which further intensifies the need for security among IoT nodes. Through the years, a significant amount of effort has been spent standardizing the communication and improving inter-operability among IoT devices. Even so, payload which is not properly secured, or impersonation of the node is still a reality, therefore, great attention still must be paid to the security model used. The main objectives of IoT security are to maintain confidentiality and integrity of the data, availability of services and authentication of the node.